Dukungan Sosial dan Postpartum Depression pada Ibu Suku Jawa - Wiyanto, Bunga Elsharon; Ambarwati, Krismi Diah (Universitas Ciputra Surabaya, 2021)
This study aims to examine the correlation between social support and postpartum depression in Javanese mother after giving birth. The hypothesis in this study there is negative relation between social support and postpartum depression in Javanese mother after giving birth. The study used a correlational quantitative research design and the research sample used purposive sampling technique on 34 Javanese mother after giving birth. The measuring instruments used are the Edinburgh Postnatal Depression Scale (EPDS) and the Postpartum Social Support Questionnaire (PSSQ). Based on the results of the study, the results of the correlation coefficient (r) = 0.138 with a value of sig = 0.219 (p <0.05), which mean there was no negative relationship between social support and postpartum depression in Javanese mothers after giving birth. Thus, the hypothesis proposed in this study is not be accepted.